Kandungan Formalin dan Jumlah Total Bakteri pada Produk Sosis di Pasar Tradisional Moga Kabupaten Pemalang Jawa Tengah - Alimi, Ramadan Nur; Ambarwanty Mohtar, Cici Farhana; Inayah, Mazidah Noer (poltekkes kemenkes pontianak, 2025)
One sort of frozen food that is made from processed meat is sausage. Formalin is one of preservative that is frequently abused, which can found in market-sold sausages. Health issues can arise from consuming foods containing formalin for an extended period of time. The filthy market environment, dust, and touch between customers' and sellers' hands can all lead to microbial contamination of food that sold in traditional markets. There has never been any prior research on the formalin content and bacterial contamination of sausage products sold in Pemalang Central Java's traditional markets. Therefore, the purpose of this study was to figure out the amount of formalin and the quantity of bacteria contaminating sausage products that are sold at Moga traditional market in Pemalang, Central Java. There were 6 samples of sausage were chosen randomly from several suppliers. A formalin test kit was used to qualitatively analyze the formalin, and the TPC method was employed for counting the bacteria. The result showed that formalin was absent from every sausage products. However, the TPC indicated that 4 of 6 sausages were contaminated with bacteria, S01, A02, S03, and S06, with counts of 1,2 × 10⁴ CFU/mL, 8.6 × 10⁴ CFU/mL, 8.7 × 10⁴ CFU/mL, and 3 × 10⁴ CFU/mL, respectively. Fortunately, the overall bacterial count remained below the acceptable level for human consumption.